1994
DOI: 10.1084/jem.179.5.1671
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of mouse CD14 expression in Kupffer cells by lipopolysaccharide.

Abstract: SummaryWestern blot analysis showed that a monoclonal antibody against recombinant mouse CD14 (mCD14), designated rmC5-3, specifically reacted with mouse macrophage cell line J774, but not myeloma cell line NS1. Fluorographic and immunocytochemical analysis demonstrated specific binding of rmC5-3 with mouse resident macrophages, inflammatory monocytes and neutrophils, and macrophage cell lines. Immunohistochemical staining using rmC5-3 showed that CD14-positive Kupffer cells (KC) were small in number in the li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
86
2
5

Year Published

1995
1995
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(101 citation statements)
references
References 27 publications
8
86
2
5
Order By: Relevance
“…Thus, in this respect liver differs from other organs belonging to the reticuloendothelial system, such as spleen or lung, which exhibit readily detectable tlr4 expression. Similarly, CD14, another LPS-recognition molecule intimately involved in the LPS-receptor complex, was also not detectable in liver of healthy mice [31,32]. Thus, under physiological conditions, the LPSreceptor and accessory molecules of the receptor complex seem to be strongly down-regulated in mouse liver.…”
Section: Discussionmentioning
confidence: 95%
“…Thus, in this respect liver differs from other organs belonging to the reticuloendothelial system, such as spleen or lung, which exhibit readily detectable tlr4 expression. Similarly, CD14, another LPS-recognition molecule intimately involved in the LPS-receptor complex, was also not detectable in liver of healthy mice [31,32]. Thus, under physiological conditions, the LPSreceptor and accessory molecules of the receptor complex seem to be strongly down-regulated in mouse liver.…”
Section: Discussionmentioning
confidence: 95%
“…A high abundance of CD14 receptors have been identified in rat peritoneal macrophages but, surprisingly, isolated KCs do not posses a large number of these receptors. 34,54 However, CD14 expression in KCs is upregulated after LPS exposure. 54 Under our experimental conditions we observed that the absence of serum (i.e., LBP) did not affect LPS-induced iNOS mRNA levels in KCs.…”
Section: Discussionmentioning
confidence: 99%
“…3A, mCD14 was not detectable on murine MC. Further, treatment with LPS, which was shown to enhance mCD14 expression in macrophages [35,36], also failed to induce detectable mCD14 expression on MC (see Supplementary Fig. 3 online).…”
Section: Activation Of MC By R-form Lps Is Independent Of Lbp and Cd14mentioning
confidence: 99%